Factors Influencing and Efforts to Improve Public Legal Awareness in Preserving the Status Quo of Crime Scenes in Kupang City - Leo , Rudepel Petrus; Bunga, Gerald Aldytia (Journal of Ecohumanism, 2024)
Objectives: This study aims to elucidate the factors influencing public legal awareness in maintaining the status quo at crime scenes, the relationship between knowledge, understanding, attitude, and legal behavior of the public in maintaining the status quo at crime scenes, and the measures taken to address public legal awareness in maintaining the status quo at crime scenes. Methods: This research is a juridical-empirical study that collects data directly from the public in Kupang City through questionnaires and interviews with 225 respondents and 3 police officers. The data were analyzed using inferential statistical techniques. Results: The factors affecting public legal awareness in maintaining the status quo at crime scenes in Kupang City are past experiences, mass media, socio-cultural values, formal education, and legal counseling. Conclusions: The relationships between indicators of legal awareness are: legal knowledge and understanding are related to the legal attitude of the public in maintaining the status quo at crime scenes; Legal attitude is related to the legal behavior of the public in maintaining the status quo at crime scenes. Government measures include preemptive and preventive efforts. To date, no cases have been addressed through repressive measures, such as cases involving intentional acts to obscure, damage, or remove evidence at crime scenes.